2022
DOI: 10.3389/fimmu.2022.939940
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomics Reveals Killing Mechanisms of Antitumor Cytotoxic CD4+ TCR-T Cells

Abstract: T cell receptor-engineered T cells (TCR-Ts) have emerged as potent cancer immunotherapies. While most research focused on classical cytotoxic CD8+ T cells, the application of CD4+ T cells in adoptive T cell therapy has gained much interest recently. However, the cytotoxic mechanisms of CD4+ TCR-Ts have not been fully revealed. In this study, we obtained an MHC class I-restricted MART-127-35-specific TCR sequence based on the single-cell V(D)J sequencing technology, and constructed MART-127-35-specific CD4+ TCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 62 publications
4
8
0
Order By: Relevance
“…The Jurkat T-cell-activation-related genes CD69 , CD82 , CD83 , DUSP2 , ANXA1 , and mCherry were upregulated in cell pairing positive 1 and positive 2 as analyzed by the UMAP plot and dot plot (Figure D). We also analyzed the single-cell profiling of primary TCR-T cells cocultured with target cells derived from Liang et al, and the T-cell-activation-related genes CD69 , CD82 , CD83 , DUSP2 , ANXA1 were upregulated in TCR-T cells stimulated by the APC pulsed with tumor antigen MART-1 (Figure S5). These results revealed that the high-throughput screening platform can screen the TCR–pMHC-specific recognition in Jurkat reporter cells through the DNA barcode and gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…The Jurkat T-cell-activation-related genes CD69 , CD82 , CD83 , DUSP2 , ANXA1 , and mCherry were upregulated in cell pairing positive 1 and positive 2 as analyzed by the UMAP plot and dot plot (Figure D). We also analyzed the single-cell profiling of primary TCR-T cells cocultured with target cells derived from Liang et al, and the T-cell-activation-related genes CD69 , CD82 , CD83 , DUSP2 , ANXA1 were upregulated in TCR-T cells stimulated by the APC pulsed with tumor antigen MART-1 (Figure S5). These results revealed that the high-throughput screening platform can screen the TCR–pMHC-specific recognition in Jurkat reporter cells through the DNA barcode and gene expression.…”
Section: Resultsmentioning
confidence: 99%
“…[ 13 ] The TCR‐5T‐3 was derived by sorting CTLs that were positive for the MART‐1 27‐35 /MHC tetramer, which was then followed by single‐cell V(D)J sequencing. [ 29 ] The mCherry fluorescence signal from the TCR‐5T‐3 was much weaker in comparison to that of the TCR‐1G4 and DMF5. (Figure 5a) as a result of the functional verification carried out using the Jurkat reporter system and the APC co‐culture in the microplate.…”
Section: Resultsmentioning
confidence: 99%
“…To validate the immunogenicity of predicted HCC neoantigens, we applied the approach of in‐vitro stimulation of antigen‐specific CTLs by DCs loaded antigen peptides. [ 5,31 ] First, we measured the cell viability and proportions of different immune cells in the commercial PBMCs by flow cytometry. The results showed that immune cells account for 98.9% of PBMCs with CD45 antibody staining, 24.6% of PBMCs are CD14 positive monocytes, CD3 positive T cells account for 51.3% of PBMCs and 54.5% of them are CD8 positive T cells, which demonstrate 28.0% in total PBMCs (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…To validate the immunogenicity of predicted HCC neoantigens, we applied the approach of in-vitro stimulation of antigenspecific CTLs by DCs loaded antigen peptides. [5,31] First, we measured the cell viability and proportions of different immune cells in the commercial PBMCs by flow cytometry. The results showed S1, Supporting Information).…”
Section: Identification Of Immunogenicity Of Hcc Neoantigen Candidate...mentioning
confidence: 99%
See 1 more Smart Citation